2008
DOI: 10.1039/b803342k
|View full text |Cite
|
Sign up to set email alerts
|

DFT study on hydroxy acid–lactone interconversion of statins: the case of atorvastatin

Abstract: Atorvastatin (ATV), the best known HMG-CoA reductase inhibitor family member, undergoes pH-dependent hydroxy acid-lactone interconversion similar to other statins. Although the only active form is a linear one, it was shown that drug interactions should also be considered for the lactone. The ATV lactonisation-hydrolysis mechanism was investigated theoretically using the density functional theory (DFT) method. Under both mildly acidic and basic conditions, the ATV lactone form is less stable than its hydroxy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
1
10
0
2
Order By: Relevance
“…Comparing the SERS and Raman spectra of (À)-Rmevalactone, the assignment of the bands in the SERS spectrum seems rather equivocal because all the signals are shifted, even about 50 cm -1 (but the calculations were not scaled). In the SERS spectrum, there are two strong bands, [26], ν C4C14 [21], ρ 1(CH3) [17], ρ 2(CH3) [10] 980 960 972 ρ C14H15H16 [27], ρ 2(CH3) [13], β 1/R6 [12], ρ 1(CH3) [9] 997 977 990 ρ C17H18H19 [25], ρ 2(CH3) [13], In the normal coordinate analysis, a nonredundant set of 51 internal coordinates was defined (Table S3, Supporting Information). The vibrations have been designated as follows: the stretching vibrations -ν (19), the six-membered ring deformations (β 1-3/R6 -in plane, τ 1-3/R6 -out-of plane) (6), the C = O group deformations (ρ C3O7 -in plane, γ C3O7 -out-of plane) (2), the methyl group deformations (β 1(CH3) -symmetric bending or umbrella vibration, β 2-3(CH3) antisymmetric bending, ρ 1-2(CH3) -rocking vibrations) (5), the "-CH 2 -" group in the ring deformations (δ -scissoring, ρ -rocking, ω -wagging, τ -twisting) (4x4), O-H bending (β C4O5H10 ) (1), and two torsions τ C4C6 and τ C4O5 (2).…”
Section: Sers Spectrum Of (à)-R-mevalonolactonementioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the SERS and Raman spectra of (À)-Rmevalactone, the assignment of the bands in the SERS spectrum seems rather equivocal because all the signals are shifted, even about 50 cm -1 (but the calculations were not scaled). In the SERS spectrum, there are two strong bands, [26], ν C4C14 [21], ρ 1(CH3) [17], ρ 2(CH3) [10] 980 960 972 ρ C14H15H16 [27], ρ 2(CH3) [13], β 1/R6 [12], ρ 1(CH3) [9] 997 977 990 ρ C17H18H19 [25], ρ 2(CH3) [13], In the normal coordinate analysis, a nonredundant set of 51 internal coordinates was defined (Table S3, Supporting Information). The vibrations have been designated as follows: the stretching vibrations -ν (19), the six-membered ring deformations (β 1-3/R6 -in plane, τ 1-3/R6 -out-of plane) (6), the C = O group deformations (ρ C3O7 -in plane, γ C3O7 -out-of plane) (2), the methyl group deformations (β 1(CH3) -symmetric bending or umbrella vibration, β 2-3(CH3) antisymmetric bending, ρ 1-2(CH3) -rocking vibrations) (5), the "-CH 2 -" group in the ring deformations (δ -scissoring, ρ -rocking, ω -wagging, τ -twisting) (4x4), O-H bending (β C4O5H10 ) (1), and two torsions τ C4C6 and τ C4O5 (2).…”
Section: Sers Spectrum Of (à)-R-mevalonolactonementioning
confidence: 99%
“…It was also found that the enantiomeric pairs of δ‐lactones differ in odor and threshold of perception . The whole class of δ‐lactones are statins, which are currently the top‐selling cholesterol‐lowering drugs in the world . Some of them, like simvastatin and lovastatin, are administered directly as δ‐lactone prodrugs, which upon conversion to their respective hydroxy acid serve as strong competitive inhibitors of 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase (HMG‐CoA reductase) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em amostras de plasma com pH acima de 6, a forma lactona fica instável e o equilíbrio favorece a hidrólise, abrindo a lactona e produzindo a forma hidroxiácido. Já a forma ácida, é suscetível sob condições mais ácidas à formação de lactona (Figura 1) (GOOSEN et al, 2007;HERMANN;CHRISTENSEN;REUBSAET, 2005;NOWOSIELSKI, 2008;XIA, 2000;MACWAN et al, 2011;TURNER et al, 2018). Cerca de 70% da atividade inibitória total da HMG-CoA redutase é explicada pelos metabólitos ativos da ATV (LENNERNÄS, 2003).…”
Section: Introdução Geralunclassified
“…O tempo de ultrafiltração representa um fator limitante para a viabilidade da análise em função da interconversão das formas ácida para as respectivas formas lactona da ATV e metabólitos. A manutenção do pH da amostra na faixa de 4 a 5 e temperatura de 4°C, minimiza a interconversão da ATV entre as formas ácida e lactona(GOOSEN et al, 2007;HERMANN;CHRISTENSEN;REUBSAET, 2005;NOWOSIELSKI, 2008;XIA, 2000; MACWAN et al, 2011;TURNER et al, 2018). Considerando que o pH do ultrafiltrado de plasma varia entre 8 e 9, a adição de solução tampão fosfato de potássio dibásico pH 7,4 permite a redução do pH, embora ainda com valores acima do pH necessário para a estabilidade das formas ácida e lactona.…”
unclassified